2022
DOI: 10.1038/s41433-022-02240-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel tool for quantitative measurement of distortion in keratoconus

Abstract: Background Keratoconus is associated with thinning and anterior protrusion of the cornea resulting in the symptoms of blurry and distorted vision. The commonly used clinical vision tests such as visual acuity and contrast sensitivity may not reflect the symptoms experienced in keratoconus and there are no quantitative tools to measure visual distortion. In this study, we used a quantitative test based on vernier alignment and field matching techniques to quantify visual distortion in keratoconus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In the examination, subjects need to judge whether adjacent lines are aligned (similar to cursor scales), and human cursor thresholds can be as low as 2 to 5 arcseconds. This method, capable of quantitatively measuring visual distortion, is often used to detect ne-level visual distortions and is frequently seen in eye diseases such as macular degeneration, glaucoma, and keratoconus [22] . Simultaneous vision, fusion vision, and stereopsis are three important functions for achieving binocular vision, widely used in clinical pediatric ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…In the examination, subjects need to judge whether adjacent lines are aligned (similar to cursor scales), and human cursor thresholds can be as low as 2 to 5 arcseconds. This method, capable of quantitatively measuring visual distortion, is often used to detect ne-level visual distortions and is frequently seen in eye diseases such as macular degeneration, glaucoma, and keratoconus [22] . Simultaneous vision, fusion vision, and stereopsis are three important functions for achieving binocular vision, widely used in clinical pediatric ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…This program builds upon clinically common classic visual function test indicators by incorporating binocular rivalry tasks, creating a comprehensive binocular vision task mode (rivalry-state visual task). Specifically, it utilizes the cursor acuity test 27 and a three-level binocular vision function test (simultaneous vision, fusion vision, and stereoscopic vision) 28 as base indicators, combined with binocular rivalry-state tasks, to construct a complete visual function screening program that can assess the presence of visual distortion and risks of binocular imbalance in complex or poor visual environments. This program includes four key tests: Rivalry-cursor visual acuity test, Rivalry-simultaneous vision test, Rivalry-fusion vision test, and Rivalry-stereoscopic vision test (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of glare sensitivity resulting in visual impairment is called disability glare, which is defined by the CIE ( Commission Internationale d'Eclairage ) as retinal straylight, a result of studies that showed that disability glare can be understood on the basis of light scattering in the eye 9 . This disability glare represents the loss of retinal image contrast as a result of intraocular light scatter, or straylight, and it is one of the most widely reported symptoms by patients with KC 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 This disability glare represents the loss of retinal image contrast as a result of intraocular light scatter, or straylight, and it is one of the most widely reported symptoms by patients with KC. 10 For those reasons, as KC progresses, not only is the perceived vision altered but also the optical quality of the eye and the patient's quality of life are affected. It is important to highlight that in moderate and advanced KC, in many cases, the loss of visual function as perceived by the patient is disproportionate to that reflected by clinical measurements.…”
mentioning
confidence: 99%